An update on the myxomycete biota (Amoebozoa: Myxogastria) of Colombia (2012)
ABSTRACT: Twelve new records of myxomycetes are reported for Colombia. These additions increase the number of myxomycetes known from this country to 108 species. Since the Colombian territory is part of a biodiversity-rich region in the heart of the Neotropics, the present effort may be considered as a minor contribution. However, due to scarcity of myxomycete research in this country and the importance of inventories involving microorganisms for such purposes as restoration ecology and ecosystem functioning projects, the data presented herein represent a necessary contribution to an understudied aspect of tropical ecology.